Breaking down the barriers: strength training in long distance triathletes - Luckin, K. M.; Badenhorst, C.; Cripps, A.; Landers, G.; Merrells, R.; Bulsara, M.; Hoyne, G. (Journal of Australian Strength and Conditioning, 2017)
Long distance triathletes complete large endurance training volumes with approximately half reporting to including some form of strength training (ST) in their program. However, the characteristics of this ST is currently unknown. Despite not all triathletes incorporating ST, research indicates that the completion of concurrent strength and endurance training in runners, cyclists and short course triathletes can significantly improve cycling and running economy and potentially reduce injury occurrence, likely resulting in performance improvements. Previous research has hypothesised barriers to ST in endurance athletes, however there is no empirical evidence to support such hypotheses. Therefore the primary aims of this investigation were to identify perceived barriers towards the completion of ST in long distance triathletes and ST characteristics. It was hypothesised that long distance triathletes would report limited time available for ST and fear of hypertrophy limiting their endurance performance as primary barriers to ST completion.